FAD DIETS: AN INTEGRATIVE REVIEW STUDY ON THE CARNIVORE DIET: dietas da moda: um estudo de revisão integrativa sobre a dieta carnívora - Eduarda Luque Pino; Rafaella Caroline de Lellis Moreira; Liv Nunes Almeida Gomes; Aline Veroneze de Mello Cesar (Revista de Ciências da Saúde Nova Esperança, 2025)
Fad diets have become increasingly popular, driven by promises of rapid weight loss, improved mood, and even disease control. Among these, the carnivore diet has gained prominence in recent years, due to the number of followers and the premise of completely excluding plant-based foods, prioritizing the consumption of meat and meat products. In this regard, this study aims to conduct an integrative review of the literature on the possible effects of the carnivore diet on human health, assessing its risks, benefits, and impacts. The methodology consisted of searching and selecting scientific articles published in the last five years in the PubMed Central (PMC) database, using the descriptors: “carnivore,” “carnivore diet,” “ketogenic diet,” “meat-based diet,” and Boolean operators (OR/OU). After applying the inclusion criteria (year, type of study, and exclusion), three studies were included in the final analysis, two of a descriptive nature and one randomized clinical trial. The findings point to possible short-term benefits, such as improved glycemic markers, but also reveal significant deficiencies in nutrients such as fiber, vitamin C, magnesium, and folate, as well as elevations in LDL cholesterol levels. The main methodological limitations of the studies included small samples, short follow-up time, and lack of a control group. There was also a shortage of robust clinical trials evaluating the long-term effects of the carnivore diet. Therefore, the results are not sufficient to recommend this dietary practice, especially in vulnerable groups. It is concluded that, despite the media appeal and popularity of the diet, dietary strategies should respect the principle of individualization, based on solid scientific evidence and considering the social, cultural, and clinical context of the individual.